Efficiency Evaluation of Different Agricultural Machinery in Rice Cultivation at Agricultural Machinery Testing and Research Centre (AMTRC), Nawalpur, Sarlahi, Nepal - Jha, Ram Nath; Ansari, Md. Shamshad; Thakur, Manish (International Journal of Bio-resource and Stress Management, 2019)
Agriculture is the mainstay of Nepalese economy. Rice is a major staple crop of the country. Mechanization in rice cultivation is the best solution to get rid of labor scarcity and increase production of rice. AMTRC has been carrying out different research works on use of different machineries and cultivation practices in rice farming. During 2017-18/2018-19, it conducted research on uses of different machineries in three replications with five treatments. The mean grain yield due to treatments in pooled analysis of two years data was found significant at 1% level. The highest mean grain yield from two years data was found 3558.33 kg ha-1 in the treatment of rice transplanted by mechanical transplanter, the lowest production of 2576.33 kg ha-1 by directly seeded with power tiller drill machine and the average yield in farmer’s practiceswas recorded as 2977.50 kg ha-1. The average of two years data revealed 12.13% more yield in the treatment-3 than the treatment-5. The variable costs became high in farmer’s practices due to more labor requirement, it was 19.36% more in treatment-5 than Treatment-3 and it ultimately affected the gross margin under farmer’s practices of rice cultivation which became low. The total gross margin was 136.19% more in treatment-3 than farmers’ practices. Thus, among the five treatments, the rice produced from the use of mechanical rice transplanter was found most profitable than other machines used in the trial including farmer’s practices in this experiment. Comparatively low gross margin was observed in other treatments.